2009
DOI: 10.1080/14017430802389537
|View full text |Cite
|
Sign up to set email alerts
|

Stroke morbidity in Swedish- and Finnish-speaking populations of Turku, Finland

Abstract: The attack rate of ischaemic stroke was lower among Swedish-speaking than among Finnish-speaking men. This difference was not totally explained by the higher SES of the Swedish-speaking population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, a recent European study found few differences between men and women in factors affecting mental well-being (Dreger et al, 2014). In addition, the same gender difference in language-groups in Finland has been observed in other areas of health, like stroke (Lammintausta et al 2009), myocardial infarction (Lammintausta et al, 2011) and mortality (Sipilä and Martikainen, 2009), and in wages and wealth (Saarela and Finnäs, 2004; Saarela, 2006). Nevertheless, further research is needed on the possible contribution of social environment to gender differences in schizophrenia.…”
Section: Discussionmentioning
confidence: 66%
“…However, a recent European study found few differences between men and women in factors affecting mental well-being (Dreger et al, 2014). In addition, the same gender difference in language-groups in Finland has been observed in other areas of health, like stroke (Lammintausta et al 2009), myocardial infarction (Lammintausta et al, 2011) and mortality (Sipilä and Martikainen, 2009), and in wages and wealth (Saarela and Finnäs, 2004; Saarela, 2006). Nevertheless, further research is needed on the possible contribution of social environment to gender differences in schizophrenia.…”
Section: Discussionmentioning
confidence: 66%
“…The Swedish-speaking minority in Finland tends to be in better health than the Finnish-speaking majority [10,40,41], and factors such as social status and social capital have been considered potential explanatory factors, though they do not completely account for differences [11,[42][43][44][45][46][47]. Anglophones in Québec have historically had higher social status [14,16], thus their higher life expectancy is not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent data concerning Transient Ischemic Attacks (TIAs) from north Savonia suggest that ischemic strokes remain relatively common in eastern Finland [122]. Previous data also show the importance of cultural factors in stroke incidence, which are evident when Swedish-speaking and Finnishspeaking Finnish men are compared (the Swedish-speaking minority also shows a lower all-cause mortality) [123][124][125]. It is, therefore, unfortunate that current data on nationwide stroke incidence and the recent trends in Finland are not available, let alone valid and comprehensive epidemiological sex-, age-and region-specific data that include variables indicating socioeconomic status, cultural associations and modifiable stroke risk factors.…”
Section: Great Unknownsmentioning
confidence: 99%